2011
DOI: 10.2136/sssaj2010.0122
|View full text |Cite
|
Sign up to set email alerts
|

Knudsen and Molecular Diffusion Coefficients for Gas Transport in Unconsolidated Porous Media

Abstract: This study was an assessment of the Knudsen and molecular diffusion cocfficienrs in relation to gas-phase permeability and air-filled porosity, respectively, for gas transport in unconsolidated porous media. Single gas How experiments at various gas pore pressures and equimolar binary experiments were conducted to determine apparent, effective gas permeabilities as well as the Knudsen and molecular diffusion coefficients. Experimental results integrated with data from previous studies showed that for dry porou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…hese magnitudes are very small in comparison with the permeability of the sandy layer (1.0 ´ 10 −11 m 2 ). his implies high resistance to gas difusion in lowpermeability zones (i.e., the cemented limestone layer), as pointed out by Davis et al (2005) and Fen et al (2011).…”
Section: Soil Intrinsic Permeabilitymentioning
confidence: 85%
See 1 more Smart Citation
“…hese magnitudes are very small in comparison with the permeability of the sandy layer (1.0 ´ 10 −11 m 2 ). his implies high resistance to gas difusion in lowpermeability zones (i.e., the cemented limestone layer), as pointed out by Davis et al (2005) and Fen et al (2011).…”
Section: Soil Intrinsic Permeabilitymentioning
confidence: 85%
“…Molins et al (2010) further demonstrated that the DGM approach (coupled with aqueous-phase transport and biogeochemical reactions) can be used to assess the concentration distributions of reactive and nonreactive gas components in an unsaturated soil above a smear zone of a crude oil spill site. If the DGM approach is used, however, another parameter, the Knudsen difusion coeicient, may also afect gas transport in soils with low permeability or at a high water content (Fen et al, 2009(Fen et al, , 2011. Being related to soil air permeability, the Knudsen difusion coeicient may also afect model ittings to soil gas concentration depth proiles where degradation occurs.…”
mentioning
confidence: 99%
“…Knudsen and molecular diffusion are two primary diffusion mechanisms that can take place during fluid flow in porous media. In general, during gas injection, the molecular diffusion occurs as a result of the collision between the molecules of the gas, while Knudsen diffusion occurs when the gas molecules collide with the rock wall and are reflected back by the rock particles. , Hence, the Knudsen diffusion is dominant when the pore diameter is less than or nearly equal to the free path of the molecules. Consequently, the Knudsen diffusion is more likely to occur in tight reservoirs, with permeability less than 10 –14 m 2 .…”
Section: Co2 Diffusion In Porous Mediamentioning
confidence: 99%